Novel targeted therapies for immunoglobulin light chain amyloidosis: latest updates from the 2024 ASH annual meeting - Bu, Qiling; Zhu, Hong-Hu; Chen, Wenming (Journal of hematology and oncology, 2025)
Immunoglobulin light chain (AL) amyloidosis is an incurable disease caused by the accumulation and sedimentation of unstable free light chains produced by monoclonal plasma cells. The key to treatment is to achieve a deep hematologic remission in order to improve organ function or reverse organ dysfunction. Conventional treatment has not been able to fully meet the treatment needs of patients with AL, while therapies targeting malignant plasma cells or amyloid have potentially improved treatment outcomes. This study provides an overview of the latest reports on targeted therapies for AL amyloidosis from the 2024 ASH Annual Meeting.